The Development of a Computer Based Education Management Information System (MIS) Model in Elementary School Bandar Lampung - Riswandi, Riswandi (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
The general objective of the research is to develop a model ofÂ a computer-based education management information systems (MIS) in Elementary schoolsÂ Â and the specific objectives were to (1) develop a prototype model of an education MIS computer-based; and (2) to develop the procedure Manual of a computer-based education MIS models. The design of the research was research and development proposed by Borg and Gall. The samples were elementary schools in the city of Bandar Lampung. The research procedure were (1) determining the location of the research, (2) collecting data, (3) designing the initial product and validating to the experts, (4) conducting a seminar in the forum group discussion (FGD), and (5) revising the first design. The result of the product is a prototype model of computer-based education MIS and the manual procedure of computer based education MIS for the elementary school.